Karakteristik Penderita Katarak Senilis di Rumah Sakit Umum Pusat Sanglah Tahun 2014 - Fransiska Lavinia Gracella; I Wayan Eka Sutyawan; A. A. Mas Putrawati Triningrat (Universitas Udayana, 2017)
The eyes are one of the senses that has an important function in life, namely as sensory vision. A pathological condition that can occur in lens is senile cataract that affected population aged >50 years. Research on senile cataract was conducted to determine the characteristics of senile cataract patients in Sanglah Hospital 2014. This study was a descriptive study using cross sectional design. The sampling technique is total sampling. The data that met the inclusion criteria will then be analyzed. Patient data were included in the criteria for inclusion are as many as 73 datas. There are 46.6% male patients and 53.4% ??of women. The age group 50-59 years, 60-69 years, 70-79 years and 80-96 years in a row as much as 31.5%, 39.7%, 24.7% and 4.1%. A total of 19.2% had cataract in the right eye, left eye cataract was 12.3%, and 68.5% cataracts in both eyes. Patients with stage Incipient 0%, as much as 74% of immature, mature as much as 24.4%, and hipermatur as much as 1.6%. There are 24.7% of patients with early visual acuity ?6/18, as many as 39.7% with visual acuity <6/18 but ?6/60, as many as 17.8% of patients respectively with visual acuity <6/60 but ? 3/60, as well as visual acuity <3/60. Patients with senile cataract comes from the city of Denpasar as much as 37%, Badung 12.3%, Bangli 2.7%, Buleleng 1.4%, Gianyar 15.1%, Jembrana 8.2%, Karangasem 8.2%, Klungkung 2.7%, Tabanan 4.1%, and those from outside the province Bali 8.2%. Most patients were female, age group 60-69 years, bilateral senile cataract, immature stage, initial visual acuity ?6/60 but <6/18, moderate visual impairment. Keyword : senile cataract, stage, bilateralitas, vision, prevalence